PENGEMBANGAN MEDIA BINTARA UNTUK MENINGKATKAN LITERASI MEMBACA PERMULAAN DALAM PEMBELAJARAN BAHASA INDONESIA - Muhammad Eko Apriliyanto; Shafa Annawa Zahra Salsabila; Salsa Hikma Ramadanta; Rani Setiawaty (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to develop and test the feasibility and practicality of BINTARA (Early Reading Application Based on Local Wisdom of Yogyakarta) as an innovative digital learning medium to improve early reading literacy skills among second-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Feasibility is evaluated by subject matter experts and media experts, while practicality is evaluated through teacher and student responses. Results: Validation showed the feasibility of BINTARA, with media experts giving a score of 86% and subject matter experts 83.5%. The practicality test resulted in a “very practical” category, with a score of 87.5% from teachers and 86% from students. The application is considered interesting, user-friendly, and appropriate for the local cultural context of Yogyakarta. Uniqueness: BINTARA innovates by integrating local Yogyakarta wisdom, historical buildings, traditions, traditional clothing, and cuisine into Android-based early reading lessons. This facilitates contextual and meaningful learning that strengthens students' character and cultural literacy.